Cues to individuation facilitate 6-month-old infants’ visual short-term memory - Cantrell, Lisa M. (Dev Psychol, 2019)
Infants’ ability to perform visual short-term memory (VSTM) tasks develops rapidly between 6 and 8 months. Here we tested the hypothesis that infants’ VSTM performance is influenced by their ability to individuate simultaneously presented objects. We used a one-shot change detection task to ask whether 6-month-old infants (N = 47) would detect a change in the color of one item in a two-item array when the stimulus context facilitated individuation of the items. In Experiment 1, the two items in the display differed in shape and color, and in Experiment 2 the onset and offset times of the two items differed. In both experiments, 6-month-old infants detected a change, contrasting with previous results. Thus, young infants’ encoding of information about individual items in multiple-item arrays is related to their ability to individuate those items.